Key Performance Indicator Merujuk pada Perspektif Proses Bisnis Internal dan Perspektif Pembelajaran dan Pertumbuhan - Akseptori, Ristanti; Yuniati, R A Norromadani; Maulana, Danis; Dewi, Murni Sari (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2022)
This study aims to optimize performance by modelling Key Performance Indicators (KPI). The method used in this study is the Human Resources Scorecard involving two perspectives, namely the internal business process perspective and the learning and growth perspective. The study results refer to two HRSC perspectives, namely the measure of performance drivers that the company can apply as a standard for evaluating the performance of employees in the Compensation and Benefits section of the HCM division. The two perspectives, namely the internal business process and the learning and growth perspectives, are categorized in yellow, meaning that performance has not yet reached the target.